Development of interactive e-comics based on ethnomathematics oriented towards students' numeracy skills - Riawan Yudi Purwoko; Wharyanti Ika Purwaningsih; Nuryadi Nuryadi (State Islamic University of North Sumatra, 2024)
The current mathematics learning process is often conducted in a blended manner, combining offline and online learning. Therefore, online learning requires instructional media that support the learning process and are appealing to students. However, the instructional media currently used to support online learning are limited and less relevant. This study aims to develop interactive mathematics learning media in the form of ethnomathematics-based e-comics that are valid, practical, and effective for middle school students. The research method employed is development research using the ADDIE model. The research subjects included middle school teachers and students. In the limited trial phase, 2 teacher and 32 students participated, while the large-scale trial involved 3 teachers and 57 students. Data collection instruments consisted of validation sheets for material and media experts, student response questionnaires, as well as pre-test and post-test questions validated by experts. Data analysis was conducted descriptively to assess the feasibility of the product. The research findings indicate that the ethnomathematics-based e-comic learning media are valid and practical. Furthermore, the e-comics meet the effectiveness criteria, as they enhance students' numeracy skills after the learning process. Therefore, the e-comics developed in this study can serve as a reference for mathematics learning media that meet current student needs.